Systems and in vitro pharmacology profiling of diosgenin against breast cancer - Khanal, Pukar; Patil, Vishal S.; Bhandare, Vishwambhar V.; Patil, Priyanka P.; Patil, B. M.; Dwivedi, Prarambh S. R.; Bhattacharya, Kunal; Harish, Darasaguppe R.; Roy, Subarna (Frontiers in Pharmacology, 2023)
Aim: The present study aimed to propose the mode of action of diosgenin against breast cancer using the series of system biology tools and verifying its outputs with experimental evidence. Methodology: The SMILES of the diosgenin were retrieved from the PubChem database and queried on 3 open-source platforms. The proteins involved in breast cancer were enriched in the STRING database and the pathways concerned with cancer progenesis were traced in the KEGG database. The diosgenin-protein(s)-pathway(s) network interaction was constructed using Cytoscape. Further molecular docking was performed using AutoDock Vina. Lead hit complexes were further evaluated via molecular dynamics, MMPBSA, principal component, and dynamics cross-correlation matrix analysis using GROMACS v2021. In addition, the various in vitro protocols like brine shrimp lethality bioassay, cytotoxicity assay, scratch assay, cell proliferation assay, and glucose uptake assay were performed to verify the computational outputs with functional biomarkers. Results: The protein-protein interaction in breast cancer had 57 edges with 5.43 average node degree with a p-value of 3.83e-14. In addition, enrichment analysis traced 36 KEGG pathways, 12 cellular components, 27 molecular functions, and 307 biological processes. In addition, cluster analysis identified 3 clusters in protein-protein interactions. In network analysis, 3 hub proteins i.e. IGF1R, MDM2, and SRC were majorly modulated in which diosgenin had the highest binding affinity with IGF1R (binding energy -8.6 kcal/mol). Further, diosgenin exhibited stable intermolecular contacts during the 150 ns MD projection run and scored the least binding free energy with IGF1R (-35.06 kcal/mol), MDM2 (-34.55 kcal/mol), and SRC (-17.90 kcal/mol). Diosgenin had the maximum cytotoxicity over MCF7 cell lines (IC50 12.05±1.33 µg/mL). In addition, the inhibitory constant (7.68±0.51) µg/mL of the diosgenin was least in MCF7 cell lines. However, the glucose uptake efficacy (EC50 15.27±0.95 µg/mL) was least in Vero cell lines compared to the rest. In addition, diosgenin chiefly inhibited the cell proliferation in SKBR3 cell lines compared to the rest. Conclusion: Diosgenin may possess the anticancer activity against the breast cancer via FoxO, PI3K-Akt, p53, Ras, and MAPK signaling pathways and modulating IGF1R, MDM2, and SRC.